Study of the risk of scheme of traffic light as risk technical system with the fault tree method - Simeonova, Tsvetelina (Yearbook Telecommunications, 2019)
The aim of the paper is to develop a methodology for risk analysis and risk assessment of a risk technical system (traffic light scheme) using the fault tree method. Results: Analysis of the risk of risk technical systems through a fault tree gives an unambiguous relationship between element parameters and parameters of equivalent elements describing a system or a part of a system. An example of risk analysis of a risk technical system (traffic light-scheme) is shown with the fault tree method applicable to students training on risk analysis and management, including a sample scheme and a tree scheme (according to accepted assumptions) and with the possibility of calculating it and determining the risk at the assumed value of the damage. Contributions: A methodology for analysis and risk assessment of risk technical systems (traffic lightscheme) has been developed and an example has been developed for the students’ training in risk analysis and management.